Impact of super high-rise buildings on wind comfort and safety of pedestrian wind environment: A case study in Shanghai, China - Fan Liu; Yanjing Ren; Lei Zhang; Xian Li (Case Studies in Thermal Engineering)
Super high-rise buildings are particularly susceptible to wind, affecting wind comfort and safety of the pedestrian environment. This study examines changes in wind environment around super high-rise buildings in Shanghai, China, before and after their construction, utilizing computational fluid dynamics. The wind speed ratio (R) was normalized across 16 cases with different wind directions. This study highlights the quantification of mean and gust wind speeds, seasonal variability, and directional wind effects as unique contributions to the comfort and safety of wind environment at a pedestrian height of 1.5 m. Results indicate that super high-rise buildings has adversely affected the local wind environment, resulting in increases in both the average wind speed and gust wind speed on the target street. After the buildings were completed, R increased significantly. The overall wind environment post-construction is classified as having a wind comfort level of Ⅱ, due to exceedance probabilities of P(V > 1.0 m/s) > 50 % and P(V > 2.5 m/s) < 2 % in summer, while the safety level is deemed acceptable. This study is based on an actual urban regeneration project involving super high-rise buildings in a Chinese megacity and is expected to clarify practical implications for urban planning and safety standards.